UNIX® Fault Management: A Guide for System Administration - Stone, Brad; Symons, Julie (Hewlett-Packard professional books., 1999)
2652E-6 Maximize UNIX system integrity and availability in mission-critical environments! If you're responsible for maintaining the integrity and availability of a mission-critical UNIX system, then you need UNIX Fault Management: A Guide for System Administrators, the first book that brings together all of the monitoring and fault management information. Expert UNIX system management engineers Brad Stone and Julie Symons show you exactly how to implement appropriate, cost-effective system monitoring on any UNIX server -- including systems configured as high availability clusters. You'll learn how to: Plan for-and establish-cost-effective, reliable system monitoring procedures Monitor systems, disks, networks, applications, and databases Detect, investigate, and recover from server problems Implement best practices for high availability in enterprise-class UNIX installations-including clusters Take advantage of key fault management trends, new standards, and new technologies This book contains detailed descriptions of fault monitoring tools and monitoring frameworks to help you make better purchasing decisions. You'll also find a handy quick reference of monitoring tasks and techniques for operators -- including specific, step-by-step recovery solutions. If you can't afford one nanosecond more downtime than necessary, you can't afford to be without UNIX Fault Management.